THE SYSTEMATIC INSCRIPTIVE OF BUGINES INTERPRETATION BOOK: COMPARATIVE ANALYSIS BETWEEN TAFSÎR AL-MUNÎR AND TAFSÎR AL-QUR’ÂN AL-KARÎM - Muhammad Dzal Anshar; Hasyim Haddade (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2020)
The Books of Tafsîr al-Munîr and Tafsîr al-Qur'ān al-Karîm are the books which compiled using Lontara script and Bugis language fully interpreting 30 Juz of Qur'ān. This research is a qualitative descriptive method which applied in the discipline of interpretation (Tafsîr) known as Muqāran by comparing two books of interpretation (Tafsîr) that are considered commensurate in order to review the differences and similarities methods used. In the systematics of the presentation, it can be concluded that the main difference between the two Books of Tafsîr Bugis is in the introduction of the interpretation (Tafsîr), whereas in Tafsîr al-Qur'ān al-Karîm begins by explaining the general description of the surah, which contains the number of surah verses, the reason for the surah name and the main topic of the surah, while in Tafsῑr al-Munῑr directly listed the verse and translation it with the title of the surah name and the number of verses at the top. In the content section of the interpretation has generally similarities in the two books of interpretation by grouping several verses based on a specific theme, in the closing section of the difference significant is found in the closing juz, each juz in Tafsir al-Munîr is closed with